Integrated laccase-producing consortium and silver nanoparticles (AgNPs)-based carbon capture microbial fuel cell (CMFC) for penicillin degradation, energy recovery, and carbon fixation - Rothjanawan, Kronsirinut; Sola, Phachirarat; Changkit, Nopparit; Chaijak, Pimprapa (Journal of Degraded and Mining Lands Management, 2026)
Antibiotic-contaminated wastewater poses a significant environmental challenge worldwide. Among the various treatment technologies, microbial fuel cells (MFCs) have attracted increasing attention due to their ability to simultaneously treat wastewater and generate electricity. In this study, a silver nanoparticle (AgNP)–based photocatalytic system was integrated with a carbon-capture microbial fuel cell (CMFC) to enhance electricity generation, carbon capture, and antibiotic removal performance. The laccase (Lac) activity and penicillin removal efficiency of a bacterial consortium were first evaluated in synthetic wastewater. Penicillin-contaminated wastewater and swine wastewater were then used as the substrate in the AgNP-based CMFC. The electrochemical performance, carbon fixation capacity, and penicillin removal efficiency of the system were systematically investigated. The results demonstrated a maximum Lac activity of 10.88 ± 0.68 U/mL and a penicillin removal efficiency of 93.15 ± 0.13% by the bacterial consortium. The AgNP-based CMFC achieved a maximum current density of 28.02 ± 0.15 A/m3, power density of 12.05 ± 0.25 W/m3, carbon fixation rate of 0.03 ± 0.01 g/L/day and penicillin removal efficiency of 93.15 ± 0.13%. These findings highlight the potential of the AgNP-based CMFC as an effective and sustainable approach for treating antibiotic-contaminated wastewater while simultaneously generating bioelectricity and capturing carbon.